RETOLD: Documenting House (Re)constructions – An Excerpt of European Approaches - Julia Heeb; George Tomegea (EXARC Journal)
As part of the EU project RETOLD, the Stadtmuseum Berlin in Germany is responsible for creating standardised documentation strategies for archaeological house models and evaluating them by engaging with the open-air museums of Astra in Romania and the Steinzeitpark Dithmarschen in Germany. In order to start creating these workflows, as a first step, other open-air museum were approached asking them to share their existing documentation forms and workflows, if any. Most open-air museums did not have existing workflows, confirming the need for this project in the first place. Of the 21 Museums approached, six did not reply, eight replied but had no standardised documentation forms and only seven did use regular documentation procedures and shared them with the project.